2017
DOI: 10.1159/000485281
|View full text |Cite
|
Sign up to set email alerts
|

Potential Targets and Clinical Value of MiR-224-5p in Cancers of the Digestive Tract

Abstract: Background/Aims: MicroRNAs participate in various biological processes in malignant tumors. However, the mechanisms of miR-224-5p in digestive system cancers are not fully understood. A comprehensive investigation of the clinical value and potential targets of miR-224-5p in cancers of the digestive tract is necessary. Methods: Expression profiling data and related-prognostic data of miR-224-5p were acquired from Gene Expression Omnibus, The Cancer Genome Atlas, ArrayExpress, and published literature. The poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…It is reported that miR‐224 acts a dual role in cancer. On the one hand, increased expression of miR‐224‐5p harbours the potential to be a diagnostic and prognostic biomarker in digestive system cancers, and is associated with the cisplatin resistance in ovarian carcinoma . On the other hand, miR‐224‐3p represses autophagy in cervical cancer by targeting FIP200 and is downregulated in multidrug‐resistant breast cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that miR‐224 acts a dual role in cancer. On the one hand, increased expression of miR‐224‐5p harbours the potential to be a diagnostic and prognostic biomarker in digestive system cancers, and is associated with the cisplatin resistance in ovarian carcinoma . On the other hand, miR‐224‐3p represses autophagy in cervical cancer by targeting FIP200 and is downregulated in multidrug‐resistant breast cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the abnormal expression of miR-224-5p was a crucial factor in the initiation and progress of tumors. For example, the high expression of miR-224-5p was likely to be involved in the onset of digestive tract malignancy ( 38 ); the expression of miR-224-5p was significantly reduced in mucinous breast cancer ( 39 ); and cell experiments and histologic examination performed by Zheng et al revealed that miR-224-5p exhibited lower expression in uveal melanoma ( 40 ). However, studies on the expression of miR-224-5p in PCa have been limited.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most of the target genes discussed above are targeted by the human-specific miR-224-5p, with the exception of TP63, targeted by miR-1246, and STK4, targeted by miR-373-3p. miR-224-5p was initially classified as a tumor suppressor [87], but it is emerging that miR-224-5p could also display oncogenic functions [88][89][90]. Very interestingly, we found that this miRNA is more expressed in the EVs from metastatic melanoma patients compared to primary cases and is absent in the EVs from healthy controls, thus being a potentially interesting biomarker of melanoma progression.…”
Section: Discussionmentioning
confidence: 63%